1997
DOI: 10.1021/jp9637284
|View full text |Cite
|
Sign up to set email alerts
|

Binding Energies of Ag+ and Cd+ Complexes from Analysis of Radiative Association Kinetics

Abstract: Association reactions of Cd+ with benzene and of Ag+ with acetone and several unsaturated hydrocarbons were observed in the Fourier-transform ion cyclotron resonance (FT-ICR) spectrometer. The reactions were presumed to occur by radiative association (RA) involving infrared photon emission, and the kinetics were analyzed to derive bond strengths for the ion−neutral complexes. To supply the structures, infrared frequencies, and infrared intensities required for this analysis, ab initio calculations at the Hartr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
78
2
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 46 publications
12
78
2
1
Order By: Relevance
“…This is demonstrated in Figure 4 by the spectrum obtained from a lithiated o functionalized PS (Quirk et al, 2009), which shows completely analogous fragments to those observed in Figure 2 from a silverated polymer. The spectral similarities most likely result from the comparable Ag þ and Li þ binding energies of PS, as expected from the very similar Ag þ and Li þ binding energies of benzene (Ho et al, 1997;Amicangelo & Armentrout, 2000). Replacement of Ag þ is necessary for the analysis of polystyrenes functionalized with easily oxidizable groups, such as Si-H (Quirk et al, 2005).…”
Section: /Zmentioning
confidence: 85%
“…This is demonstrated in Figure 4 by the spectrum obtained from a lithiated o functionalized PS (Quirk et al, 2009), which shows completely analogous fragments to those observed in Figure 2 from a silverated polymer. The spectral similarities most likely result from the comparable Ag þ and Li þ binding energies of PS, as expected from the very similar Ag þ and Li þ binding energies of benzene (Ho et al, 1997;Amicangelo & Armentrout, 2000). Replacement of Ag þ is necessary for the analysis of polystyrenes functionalized with easily oxidizable groups, such as Si-H (Quirk et al, 2005).…”
Section: /Zmentioning
confidence: 85%
“…Thus, in [5][6][7] it was shown that there is good agreement between the results of nonempirical quantum-chemical calculations of the bonding energy in Ag(I)-olefin complexes and the experimental data. In addition, it was shown for the complex of silver(I) with ethylene as a result of theoretical calculation of the highest level [8] that the complex conforms fully to the classical Dewar -Chatt -Duncanson model [2][3][4].…”
mentioning
confidence: 54%
“…The binding energy of the complexes is calculated from the following equation Equation 3 (Ho, Yang, Klippenstein, & Dunbar, 1997).…”
Section: The Binding Energy For Mgo-metal Hydrate Complexesmentioning
confidence: 99%